International scholarly research notices (Wiley, 2019)
International Scholarly Research Notices is a peer-reviewed, open access journal covering a wide range of subjects in science, technology, medicine, and social sciences. The journal’s Editorial Board as well as its Table of Contents are divided into 110 subject areas that are covered within the journal’s scope. International Scholarly Research Notices has been established in mid 2014 by merging the individual journals of the ISRN series into a single journal. The journal shall start publication on July 1st, 2014.
Gesehen am 13.08.25
Keywords: Zeitschrift